Development and Optimization of Novel Microwave-Assisted Extraction for Rich-Flavonoids and Polyphenols from Dioscorea bulbifera Leaves by Response Surface Methodology - Reddy, Soma Uday Kumar; Jyothi, Divya; Veetil, Krishna Kana; Shreya, Shreya; Sultana, Rokeya; Priya, Sneh (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: Microwave-Assisted Extraction (MAE) has emerged as a promising technique for the extraction of bioactive compounds from plant materials due to its efficiency and reduced processing time. In the present study, variables of MAE were optimized for maximizing the extraction of polyphenolic and flavonoid constituents from Dioscorea bulbifera leaves by Box-Behnken Design (BBD) of response surface methodology. Materials and Methods: Box-Behnken Design (BBD) was utilized to find the optimal microwave extraction condition for obtaining extracts enriched with polyphenolic compounds. The independent variables for BBD are irradiation power (400-800W), time (1-5 min) and concentration of ethanol (20-60%). Total phenolic content and total flavonoid content were estimated by the Folin ciocalteu method and aluminium chloride colorimetric assay respectively. Using qualitative chemical testing and FTIR analysis, the phytoconstituents and functional properties of the extracts were determined. Results: The ANOVA results obtained from the design of expert software exhibited that Total Phenolic Content (TPC) and total flavonoid content were significantly (p<0.0001) affected by microwave power of irradiation, time and concentration of ethanol, indicating good agreement between the experiment and predicted values. The ideal parameter of MAE for maximum yield of TPC (3.49 mg GAE/g) and TFC (0.61 mg QE/g) were 400W of microwave power, 5 min of irradiation time and 48.467% ethanol concentration. Conclusion: The optimized extracts can be used as a source of antioxidants with potential applications in functional foods, dietary supplements and pharmaceutical formulations aimed at combating oxidative stress-related diseases.
Keywords: Optimization; Polyphenols; Microwave; Box-Benkhen design